MANAJEMEN PENERIMAAN PESERTA DIDIK BARU (PPDB) SISTEM ZONASI - ST Nurjaningsih (Universitas Pendidikan Indonesia, 2021)
New students admission (PPDB) zoning system policy is considered ineffective in achieving goal of equitable education access and services in Indonesia. And also considered unable to eliminate people's views about favorite schools, especially in SMA Negeri 2 Tasikmalaya which has huge enthusiasts, and there were registrants buildup, so that PPDB services held by schools became less than optimal. This research means to describe management of implementation PPDB zoning system in SMA Negeri 2 Tasikmalaya, including planning, organizing, actuating, and controlling. This research used qualitative methods with descriptive approach. The data sources were head of the branch education office regional XII, vice principal, and committee of PPDB. The data collection used interviews, and documentation study techniques. The results showed that: 1) PPDB zoning system planning including understanding of applicable policy, determination requirements, capacity and zoning, budgeting, and socialization. 2) PPDB zoning system organizing is done by departmentalization based on dividing division of main tasks and functions of each committee, and adjusted to school needs. 3) PPDB zoning system actuating including registration, data input, data verification, selection, announcement of selection results, and re-registration. 4) PPDB zoning system controlling is implemented by the controlling team, head master, branch of education office regional XII, West Java Provincial Education Office, mass media and public users of PPDB services. Based on the research results, it was found that schools were not fully ready for implementing PPDB zoning system because there were advantages and disadvantages. So, it needs a massive sosialization to the public and an evaluation for improving this zoning policy.